The Interplay Between Laos as Landlocked State and its Surrounding Coastal States - Indriyani, Rachma; Budyatmojo, Winarno; Rahman, Andi; Sudarso, Thomas (Yustisia, 2017)
This paper analyzes the problems concerning Laos as a Land-locked state (LLS) rights to gain access of the sea and its resources, including conflicts and disadvantages which may arise regarding Laos and its neighboring states and/or transit states to figure out the best way to get access to fisheries at the sea. We used some legal research methods of case studies and normative doctrines which lead us to discover the rights of landlocked states provided by the UNCLOS being violated or constrained by technical problems and the denial of free transit which is highly influenced by international relation between states. This study concludes that the rights must necessarily be supported with another bilateral/multilateral agreements and organization which may help to manage landlocked states in effort of the realization of their rights.